Epoxy resin composite Sn-Bi lead-free solder paste
By adding epoxy resin, Ag powder and metal Ga to Sn-Bi lead-free solder paste, and optimizing the ratio, an epoxy resin composite Sn-Bi lead-free solder paste with excellent high temperature, high humidity and cold and thermal shock reliability was prepared. , solves the problem of insufficient performance of existing solder paste in these aspects, and achieves higher welding reliability and shear strength.
Patent Information
- Application Number
- CN202011173307.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-10-28
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2040-10-28
AI Technical Summary
The existing epoxy resin composite Sn-Bi solder paste still cannot meet the needs of new electronic products in terms of high temperature and high humidity reliability and hot and cold impact reliability.
By adding 3% to 10% epoxy resin composition, 0.001% to 1.5% Ag powder and 0.001% to 0.5% metal Ga into Sn-Bi lead-free solder paste, the proportion of each component is optimized to prepare Developed epoxy resin composite Sn-Bi lead-free solder paste with excellent high temperature and high humidity reliability and thermal and cold shock reliability.
It significantly improves the shear strength and reliability of the soldered joint, especially its performance under high temperature, high humidity and hot and cold shock conditions, meeting the needs of reflow soldering of components in the electronics industry.
Smart Images

Figure CN114473290B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a brazing material in the field of metallurgy, in particular to an epoxy resin composite Sn-Bi solder paste. Background Art
[0002] With the rapid upgrading of electronic products, the requirements for electronic packaging technology, especially in the field of micro-nano connection, are getting higher and higher. While the size of micro-solder points needs to be smaller and smaller, the force, electricity and heat loads that the welding parts need to bear are increasing day by day, so higher and higher requirements are put forward for the reliability and efficiency of brazing joints.
[0003] The research results show that welding materials, packaging substrates and bottom fillers all have an impact on the heat dissipation performance of chip-level packaged LEDs. Through calculation, the influence factor of welding materials is 8.54, which shows that improving the performance of welding materials is of great significance to the performance of LED products and many electronic devices, and even product reliability.
[0004] In view of the particularity of LED products, the solder used in its manufacturing process should be Sn-Bi solder with a lower melting point. Although the tensile strength and creep resistance of Sn-Bi solder are better than those of Sn-Pb solder, making Sn-Bi solder have great advantages in temperature-sensitive areas and outer layer soldering connections of graded packages, the hard and brittle Bi-rich phase is easy to crystallize and form a coarse, long strip / block-shaped irregular structure during the cooling process of the liquid Sn-Bi solder, resulting in the brittleness of the alloy increasing with the increase of the Bi phase content, which reduces its plasticity, and the reliability of the solder joint cannot meet the connection needs of new electronic products that are emerging with each passing day.
[0005] CN109175771A discloses an "epoxy resin composite Sn-Bi solder paste", and CN108971794A discloses a "composite Sn-Bi lead-free solder paste containing epoxy resin". The above inventions all use epoxy resin and Sn-Bi lead-free solder paste to compound, and prepare a composite Sn-Bi lead-free solder paste with higher "solder joint shear strength" through reasonable matching and optimized combination of Sn-Bi lead-free solder paste, epoxy resin, curing agent, and accelerator. However, the above epoxy resin composite Sn-Bi solder paste still has shortcomings, especially in important technical indicators such as "high temperature and high humidity reliability" and "cold and hot shock reliability", and still cannot meet the growing and rapidly developing needs of new electronic product manufacturing.
[0006] However, it is well known that high reliability of solder joints is a key technical indicator to ensure the long service life of electronic devices. In addition to high strength of the solder joints, high solder joint reliability must also have excellent high temperature and high humidity reliability and thermal shock reliability. Therefore, it is urgent to develop a solder paste with excellent high temperature and high humidity reliability and thermal shock reliability. Summary of the invention
[0007] In view of the above problems existing in the prior art, one of the objects of the present invention is to provide an epoxy resin composite Sn-Bi lead-free solder paste, which has good wetting and spreading properties, high shear strength of the solder joint, and has significant advantages in important technical indicators such as high temperature and high humidity reliability, and hot and cold shock reliability.
[0008] To achieve the above-mentioned purpose, the present invention provides an epoxy resin composite Sn-Bi lead-free solder paste, which comprises the following components by mass percentage:
[0009] Epoxy resin composition, 3%-10%;
[0010] Ag powder, 0.001% to 1.5%;
[0011] Metal Ga, 0.001% ~ 0.5%;
[0012] Sn-Bi lead-free solder paste, balance;
[0013] The epoxy resin composition is composed of epoxy resin, curing agent and accelerator in a mass ratio of 100:10-32:0.5-8.
[0014] In the above-mentioned epoxy resin composite Sn-Bi lead-free solder paste provided by the present invention, Ag powder and metal Ga are added on the basis of the epoxy resin composition and the Sn-Bi lead-free solder paste, and the ratio of the above-mentioned components and the ratio of the components in the epoxy resin composition are optimized. Compared with the existing Sn-Bi lead-free solder paste, it not only has good wetting and spreading performance, but also can significantly improve the shear strength and reliability of the solder joint, especially the high temperature and high humidity reliability and the cold and hot shock reliability, and can be used for the reflow soldering of components in the electronics industry. In addition, the trace metal Ga added in the solder paste can effectively produce a "synergistic effect" with the Ag element, and improve the high temperature and high humidity reliability and the cold and hot shock reliability of the epoxy resin composite solder paste. It can be seen from the Ag-Ga binary phase diagram that metal Ga and Ag elements can generate Ag-Ga intermetallic compounds, which can effectively avoid the problem of deterioration of the wetting performance of the solder paste during reflow soldering due to the formation of stable AgCl by trace Cl ions present in the flux and Ag ions.
[0015] The epoxy resin composite Sn-Bi lead-free solder paste described in the present invention is preferably such that the epoxy resin composition has a mass percentage of 3%, the mass ratio of the epoxy resin, the curing agent and the accelerator is: epoxy resin: curing agent: accelerator = 100:10:0.5, the Ag powder is 0.001%, and the metal Ga is 0.5%.
[0016] The epoxy resin composite Sn-Bi lead-free solder paste described in the present invention is preferably such that the epoxy resin composition has a mass percentage of 5%, the mass ratio of the epoxy resin, the curing agent and the accelerator is: epoxy resin: curing agent: accelerator = 100:15:1.5, the Ag powder is 0.1%, and the metal Ga is 0.1%.
[0017] The epoxy resin composite Sn-Bi lead-free solder paste described in the present invention is preferably such that the epoxy resin composition has a mass percentage of 7%, the mass ratio of the epoxy resin, the curing agent and the accelerator is: epoxy resin: curing agent: accelerator = 100:25:6, the Ag powder is 0.5%, and the metal Ga is 0.01%.
[0018] The epoxy resin composite Sn-Bi lead-free solder paste described in the present invention is preferably such that the epoxy resin composition has a mass percentage of 10%, the mass ratio of the epoxy resin, the curing agent and the accelerator is: epoxy resin: curing agent: accelerator = 100:32:8, the Ag powder is 1.5%, and the metal Ga is 0.001%.
[0019] The epoxy resin composite Sn-Bi lead-free solder paste of the present invention, wherein the epoxy resin preferably includes at least one of NPEL-134 novolac epoxy resin, NPEL-127H bisphenol A, E44 bisphenol A and E51 bisphenol A.
[0020] In the epoxy resin composite Sn-Bi lead-free solder paste of the present invention, the curing agent preferably includes at least one of aromatic polyamines, alicyclic polyamines and dicyandiamide.
[0021] In the epoxy resin composite Sn-Bi lead-free solder paste of the present invention, the accelerator preferably includes at least one of SH-A80, SH-A85, SH-A90 and SH-A95.
[0022] The epoxy resin composite Sn-Bi lead-free solder paste of the present invention is preferably a Sn-Bi lead-free solder paste containing P, and the Sn-Bi lead-free solder paste contains 85% to 95wt% of Sn-Bi alloy powder and the remainder of flux.
[0023] The above-mentioned Sn-Bi lead-free solder paste can be selected from commercially available Sn-Bi lead-free solder paste, or homemade Sn-Bi lead-free solder paste can be selected.
[0024] The epoxy resin composite Sn-Bi lead-free solder paste of the present invention is preferably such that, in the Sn-Bi alloy powder, by mass percentage, the Bi element content is 33% to 60%, the P content is 0.001% to 0.1%, and the balance is Sn.
[0025] The Sn-Bi alloy powder can be commercially available Sn-Bi alloy powder or homemade Sn-Bi alloy powder. Commercially available or homemade alloy powder can be prepared into Sn-Bi lead-free solder paste by conventional methods.
[0026] In the epoxy resin composite Sn-Bi lead-free solder paste of the present invention, the particle diameter of the Sn-Bi alloy powder is preferably 15 μm to 65 μm.
[0027] In the epoxy resin composite Sn-Bi lead-free solder paste of the present invention, the soldering flux is preferably ECO Flux823 or LFD.
[0028] In the epoxy resin composite Sn-Bi lead-free solder paste of the present invention, the particle diameter of the Ag powder is preferably 15 μm to 65 μm.
[0029] In the epoxy resin composite Sn-Bi lead-free solder paste of the present invention, the adding temperature of the metal Ga is preferably 80°C±5°C.
[0030] The beneficial effects of the present invention are as follows:
[0031] (1) The present invention adds 3% to 10% epoxy resin composition, 0.001% to 1.5% Ag powder, and 0.001% to 0.5% Ga to Sn-Bi lead-free solder paste to prepare epoxy resin composite solder paste. Compared with the existing Sn-Bi lead-free solder paste, it not only has good wetting and spreading performance, but also can significantly improve the shear strength and reliability of the solder joint, especially the high temperature and high humidity reliability and the thermal shock reliability, and can be used for the reflow soldering of components in the electronic industry.
[0032] (2) The epoxy resin composite Sn-Bi lead-free solder paste of the present invention has a curing time of less than 5 minutes. During reflow soldering, curing can be completed when the peak temperature residence time is within 5 minutes; when the peak temperature residence time is more than 5 minutes and less than 10 minutes, there is no effect on the solder joint strength and solder joint morphology, so that the epoxy resin cured under reflow soldering conditions can greatly improve the shear strength of the Sn-Bi lead-free solder paste solder joints, and can meet the process requirements of mass production of different reflow soldering production lines.
[0033] (3) The trace amount of metallic Ga added in the present invention can effectively produce a "synergistic effect" with the Ag element, thereby improving the high temperature and high humidity reliability and the thermal shock reliability of the epoxy resin composite solder paste. It can be seen from the Ag-Ga binary phase diagram that metallic Ga and the Ag element can generate Ag-Ga intermetallic compounds, which can effectively avoid the problem of deterioration of the wetting performance of the solder paste during reflow soldering due to the formation of stable AgCl by the trace amount of Cl ions in the flux and the Ag ions.
[0034] (4) The epoxy resin composite Sn-Bi solder paste provided by the present invention still has excellent wetting, spreading properties and solder joint mechanical properties after being stored for one year. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 The test results of high temperature and high humidity aging effects on solder paste solder joints of Example 1 and Comparative Example 1 are as follows;
[0036] Figure 2 The test results of the hot and cold cycle influence rules of the solder paste solder joints of Example 1 and Comparative Example 1 are as follows;
[0037] Figure 3 The test results of high temperature and high humidity aging effects on solder paste solder joints of Example 2 and Comparative Example 2 are as follows;
[0038] Figure 4 The test results of the hot and cold cycle influence rules of the solder paste solder joints of Example 2 and Comparative Example 2 are as follows;
[0039] Figure 5 The test results of high temperature and high humidity aging effects on solder paste solder joints of Example 3 and Comparative Example 3 are as follows;
[0040] Figure 6 The test results of the hot and cold cycle influence rules of the solder paste solder joints of Example 3 and Comparative Example 3 are as follows;
[0041] Figure 7 The test results of high temperature and high humidity aging effects on solder paste solder joints of Example 4 and Comparative Example 4 are as follows;
[0042] Figure 8 These are the test results of the influence of hot and cold cycles on solder paste solder joints of Example 4 and Comparative Example 4. DETAILED DESCRIPTION
[0043] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0044] In some embodiments, the present invention may use homemade Sn-Bi alloy powder, and the conventional preparation method of the Sn-Bi alloy powder (i.e. Sn-Bi lead-free solder) is as follows:
[0045] Use commercially available tin ingots, bismuth ingots, tin-phosphorus alloys, and silver powder, and mix various elemental raw materials as required. Add a covering agent determined by optimization screening during smelting, or use inert gas protection for smelting and casting to obtain rods. After the smelted Sn-Bi alloy (rods) are melted, the Sn-Bi alloy is prepared into alloy powder with a particle diameter of 15μm to 65μm through gas atomization powder making equipment under argon protection.
[0046] Among them, the total amount (mass percentage) of lead (i.e. Pb) element as an impurity element in the raw materials is controlled within the range of Pb≤0.07wt.% to meet the requirements of the National Standard of the People's Republic of China GB / T20422-2018 "Lead-free Solder" (the standard stipulates Pb≤0.07wt.%).
[0047] In some embodiments, the present invention may use homemade (or commercially available) Sn-Bi lead-free solder paste. In this case, the preparation method of the epoxy resin composite Sn-Bi lead-free solder paste of the present invention is as follows:
[0048] (1) Add 85% to 95% by mass of Sn-Bi alloy powder and the remainder of flux (such as ECO Flux 823 or LED) to an appropriate amount of ethanol or ethylene glycol, and stir for 10 min. to 30 min. using a high-speed stirrer (speed of 300 r / min to 1200 r / min) to obtain Sn-Bi lead-free solder paste.
[0049] (2) Prepare Ag powder (particle diameter of 15 μm to 65 μm) according to the method for preparing Sn-Bi alloy powder. Of course, as another option, commercially available Ag powder (particle diameter of 15 μm to 65 μm) can also be purchased for standby use. Add an appropriate amount of ethanol or ethylene glycol to the above-mentioned Sn-Bi lead-free solder paste, add Ag powder according to the ratio requirements, and continue stirring for more than 10 minutes. This completes the addition of Ag to the Sn-Bi lead-free solder paste.
[0050] (3) Weigh the amount of metal Ga to be added according to the ratio requirements, heat the metal Ga and the Sn-Bi lead-free solder paste with added Ag powder to 80℃±5℃ respectively, mix the liquid metal Ga with the Sn-Bi lead-free solder paste with added Ag powder, continue to stir at high speed for 5-10 minutes., cool, and the addition of metal Ga is completed (it is called Sn-Bi lead-free solder paste containing Ag and Ga). Since the melting point of Ga is only 29.8℃, the boiling point is as high as 2403℃, and Ga is not easily oxidized, it is very convenient to evenly add metal Ga to the Sn-Bi solder paste.
[0051] (4) Pre-mix epoxy resin, curing agent and accelerator according to the ratio of epoxy resin: curing agent: accelerator = 100: 10-32: 0.5-8 and mix them evenly for use (i.e. epoxy resin composition). Then, according to the ratio requirements, mix the epoxy resin composition and the remaining amount of the above-prepared Sn-Bi lead-free solder paste containing Ag and Ga, add an appropriate amount of ethanol or ethylene glycol, use a high-speed stirrer (speed of 300r / min-1200r / min) to stir for 10min.-30min., and let it stand for 10 minutes to obtain the epoxy resin composite Sn-Bi lead-free solder paste described in the present application.
[0052] The epoxy resin includes at least one of NPEL-134 novolac epoxy resin, NPEL-127H bisphenol A, E44 bisphenol A and E51 bisphenol A; the curing agent includes at least one of aromatic polyamines, alicyclic polyamines and dicyandiamide; and the accelerator includes at least one of SH-A80, SH-A85, SH-A90 and SH-A95.
[0053] Among them, in the Sn-Bi alloy powder, the Bi element content is 33wt% to 60wt%, the P content is 0.001wt% to 0.1wt%, and the balance is Sn. The product epoxy resin composite Sn-Bi lead-free solder paste contains 0.001wt% to 1.5wt% of Ag, 0.001wt% to 0.5wt% of Ga, 3wt% to 10wt% of epoxy resin composition, and the balance is Sn-Bi lead-free solder paste.
[0054] In some embodiments, according to the ratio requirements, the present invention can also use homemade (or commercially available) Sn-Bi alloy powder to first prepare Sn-Bi lead-free solder paste, and then add epoxy resin, curing agent and accelerator to prepare Sn-Bi lead-free solder paste containing epoxy resin composition, and then add Ag powder and metal Ga to prepare the epoxy resin composite Sn-Bi lead-free solder paste described in this application. The epoxy resin composite Sn-Bi lead-free solder paste prepared by this embodiment is equivalent to the epoxy resin composite Sn-Bi lead-free solder paste prepared by first adding Ag powder and metal Ga and then adding epoxy resin composition. The specific preparation steps can be described as follows:
[0055] (1) Add 85% to 95% by mass of Sn-Bi alloy powder and the remainder of flux (such as ECO Flux 823 or LED) to an appropriate amount of ethanol or ethylene glycol, and stir for 10 min. to 30 min. using a high-speed stirrer (speed of 300 r / min to 1200 r / min) to obtain Sn-Bi lead-free solder paste.
[0056] (2) Epoxy resin, curing agent and accelerator are pre-mixed in the ratio of epoxy resin: curing agent: accelerator = 100: 10-32: 0.5-8 and mixed evenly for use (i.e. epoxy resin composition). Then, according to the ratio requirements, the epoxy resin composition and the remaining amount of the Sn-Bi lead-free solder paste prepared above are mixed, and an appropriate amount of ethanol or ethylene glycol is added. The mixture is stirred for 10 min. to 30 min. using a high-speed stirrer (speed of 300 r / min to 1200 r / min), and allowed to stand for 10 minutes to obtain the Sn-Bi lead-free solder paste containing the epoxy resin composition.
[0057] (3) Prepare Ag powder (particle diameter of 15 μm to 65 μm) according to the method for preparing Sn-Bi alloy powder. Of course, as another option, commercially available Ag powder (particle diameter of 15 μm to 65 μm) can also be purchased for standby use. Add an appropriate amount of ethanol or ethylene glycol to the above-mentioned Sn-Bi lead-free solder paste containing the epoxy resin composition, add Ag powder according to the ratio requirements, and continue stirring for more than 10 minutes. The addition of Ag to the Sn-Bi lead-free solder paste containing the epoxy resin composition is completed.
[0058] (4) Weigh the amount of metal Ga to be added according to the ratio requirements, heat the metal Ga and the Sn-Bi lead-free solder paste added with the epoxy resin composition and Ag powder to 80°C±5°C respectively, mix the liquid metal Ga with the Sn-Bi lead-free solder paste added with the epoxy resin composition and Ag powder, continue to stir at high speed for 5-10 minutes, cool, and the addition of metal Ga is completed to obtain the epoxy resin composite Sn-Bi lead-free solder paste described in the present application. Since the melting point of Ga is only 29.8°C, but the boiling point is as high as 2403°C, and Ga is not easily oxidized, it is very convenient to evenly add metal Ga to the Sn-Bi solder paste.
[0059] The epoxy resin includes at least one of NPEL-134 novolac epoxy resin, NPEL-127H bisphenol A, E44 bisphenol A and E51 bisphenol A; the curing agent includes at least one of aromatic polyamines, alicyclic polyamines and dicyandiamide; and the accelerator includes at least one of SH-A80, SH-A85, SH-A90 and SH-A95.
[0060] Among them, in the Sn-Bi alloy powder, the Bi element content is 33wt% to 60wt%, the P content is 0.001wt% to 0.1wt%, and the balance is Sn. The product epoxy resin composite Sn-Bi lead-free solder paste contains 0.001wt% to 1.5wt% of Ag, 0.001wt% to 0.5wt% of Ga, 3wt% to 10wt% of epoxy resin composition, and the balance is Sn-Bi lead-free solder paste.
[0061] Example 1
[0062] (1) Add an appropriate amount of ethanol to the commercially available Sn-Bi lead-free solder paste EcoLM-C10X, then add Ag powder according to the ratio requirements, and continue stirring for more than 10 minutes to complete the addition of Ag to the Sn-Bi lead-free solder paste.
[0063] The commercially available Sn-Bi lead-free solder paste EcoLM-C10X contains 85wt% Sn-Bi alloy powder and the remaining flux ECO Flux 823. In the Sn-Bi alloy powder, Bi element accounts for 55wt% of the alloy powder, P accounts for 0.001wt%, and the remaining is Sn. In addition, the alloy powder particle diameter is 15μm to 65μm.
[0064] The particle diameter of the Ag powder is 15 μm to 65 μm.
[0065] (2) Weigh metal Ga, heat the metal Ga and the Sn-Bi lead-free solder paste added with Ag powder to 80°C±5°C respectively, then mix the obtained liquid metal Ga with the Sn-Bi lead-free solder paste added with Ag powder, continue to stir at high speed for 8 minutes, and cool. In this way, the addition of metal Ga to the Sn-Bi lead-free solder paste is completed, and the Sn-Bi lead-free solder paste containing Ag and Ga is obtained.
[0066] Among them, since the melting point of Ga is only 29.8°C, but the boiling point is as high as 2403°C, and Ga is not easily oxidized, the above method can be used to easily and evenly add metal Ga into the Sn-Bi lead-free solder paste.
[0067] (3) The epoxy resin is composed of NPEL-134 novolac epoxy resin and E51 bisphenol A in a mass ratio of 1:1; the curing agent is composed of aromatic polyamine and alicyclic polyamine in a mass ratio of 1:2; and the accelerator is composed of SH-A80 and SH-A95 in a mass ratio of 1:3. Then, the epoxy resin, curing agent and accelerator are pre-mixed according to the ratio of epoxy resin: curing agent: accelerator = 100:10:0.5 and mixed evenly to obtain an epoxy resin composition.
[0068] (4) According to the ratio requirements, the epoxy resin composition and the Sn-Bi lead-free solder paste containing Ag and Ga are mixed, and an appropriate amount of ethanol is added. The mixture is stirred for 20 minutes using a high-speed stirrer (speed of 500 r / min to 800 r / min), and allowed to stand for 10 minutes to obtain the epoxy resin composite Sn-Bi lead-free solder paste.
[0069] The product epoxy resin composite Sn-Bi lead-free solder paste contains 0.001wt% Ag, 0.5wt% Ga, 3wt% epoxy resin composition, and the remainder is commercially available Sn-Bi lead-free solder paste EcoLM-C10X.
[0070] This embodiment 1 performs reflow soldering evaluation, specifically using the following two methods:
[0071] (1) When evaluating the solder paste effect through reflow soldering, R0603 chip resistor components are used for reflow soldering. The specific test method is: select FR-4 laminate with stable electrical insulation performance, the pad is made of copper, the surface treatment process is OSP, and the soldering test process is completed within 3 days after the circuit board is unpacked. Reflow soldering is carried out under the conditions of peak temperature of 190℃ and heat preservation for 5min.
[0072] The samples (several R0603 chip resistors soldered on the PCB board) that have been cooled after reflow soldering are evenly suspended and placed in a KTHE-715TBS high temperature and high humidity test chamber.
[0073] The test parameters were determined according to the JEDEC industrial standard JESD22A101 "Steady State Temperature Humidity Bias Life Test", and the high temperature and high humidity test conditions were set to 85°C ± 2°C / 85 ± 2% RH, and the aging time was 168h, 500h and 1000h.
[0074] (2) When evaluating the solder paste effect through reflow soldering, R0603 chip resistor components are used for reflow soldering. The specific test method is: select FR-4 laminates with stable electrical insulation performance, the pads are made of copper, the surface treatment process is OSP, and the soldering test process is completed within 3 days after the circuit board is unpacked. Reflow soldering is carried out under the conditions of peak temperature of 190℃ and heat preservation for 5min.
[0075] The samples (several R0603 chip resistors soldered on the PCB board) that have been cooled after reflow soldering are evenly suspended and placed in a KSKC-415TBS temperature shock test box.
[0076] According to the JEDEC industrial standard JESD22A104 "Temperature cycling", the temperature thermal cycle conditions are set to (-40 ~ +125) ° C, each cycle is 70 minutes, the high and low temperatures stay for 30 minutes each, and the cycle is 200 cycles, 500 cycles, 750 cycles and 1000 cycles.
[0077] Comparative Example 1
[0078] The difference from Example 1 is that Ag powder, Ga metal and epoxy resin composition are not added to the commercially available Sn-Bi lead-free solder paste EcoLM-C10X.
[0079] The reflow evaluation results of Example 1 and Comparative Example 1 are shown in Figure 1 and Figure 2 .Depend on Figure 1 It can be seen that the epoxy resin composite Sn-Bi lead-free solder paste obtained in Example 1 has a point shear strength increased from 33.77N to 48.1N compared with the Sn-Bi lead-free solder paste obtained in Comparative Example 1, with an increase of more than 42%. After high temperature and high humidity aging for 1000h, the solder joint strength of the epoxy resin composite Sn-Bi lead-free solder paste obtained in Example 1 is still higher than that of the Sn-Bi lead-free solder paste obtained in Comparative Example 1. Figure 2 It can be seen that the epoxy resin composite Sn-Bi lead-free solder paste obtained in Example 1 has a solder joint shear strength increased from 33.77N to 48.1N relative to the Sn-Bi lead-free solder paste obtained in Comparative Example 1, with an increase of more than 42%. After 1000 cycles of thermal shock test, the solder joint strength of the epoxy resin composite Sn-Bi lead-free solder paste obtained in Example 1 is still higher than that of the Sn-Bi lead-free solder paste obtained in Comparative Example 1. It can be seen that the epoxy resin composite Sn-Bi solder paste obtained in Example 1 not only has good wetting and spreading performance, but also can significantly improve the shear strength and reliability of the solder joint, especially the high temperature and high humidity reliability and thermal shock reliability, and can be used for reflow soldering of components in the electronics industry.
[0080] At the same time, with FR-4 PCB board as the test board and 1210 chip resistor as the test element, reflow soldering was carried out under the conditions of peak temperature of 190°C and heat preservation for 5 minutes. The shear strength of the solder joint of the epoxy resin composite Sn-Bi lead-free solder paste of Example 1 was improved by 8% compared with the highest solder joint shear strength of the embodiments disclosed in the document CN109175771A and the document CN108971794A.
[0081] Example 2
[0082] The difference from Example 1 is that:
[0083] The commercially available Sn-Bi lead-free solder paste EcoLM-C10X contains 95wt% Sn-Bi alloy powder and the remainder flux LFD, and in the Sn-Bi alloy powder, Bi element accounts for 60wt% of the alloy powder, P accounts for 0.1wt%, and the remainder is Sn. In addition, the alloy powder particle diameter is 15μm to 65μm.
[0084] In the epoxy resin composition, the epoxy resin is E44 type bisphenol A; the curing agent is dicyandiamide; the accelerator is SH-A90. The mass ratio of the epoxy resin, the curing agent and the accelerator is: epoxy resin: curing agent: accelerator = 100:32:8.
[0085] The obtained epoxy resin composite Sn-Bi lead-free solder paste contains 1.5wt% Ag, 0.001wt% Ga, 10wt% epoxy resin composition, and the remainder is commercially available Sn-Bi lead-free solder paste EcoLM-C10X.
[0086] Comparative Example 2
[0087] The difference from Example 2 is that no Ag powder, Ga metal and epoxy resin composition are added to the commercially available Sn-Bi lead-free solder paste EcoLM-C10X.
[0088] The reflow evaluation results of Example 2 and Comparative Example 2 are shown in Figure 3 and Figure 4 .Depend on Figure 3 It can be seen that the epoxy resin composite Sn-Bi lead-free solder paste obtained in Example 2 has a solder joint shear strength increased from 33.77N to 50.31N compared with the Sn-Bi lead-free solder paste obtained in Comparative Example 2, with an increase of more than 48.9%. After high temperature and high humidity aging for 1000h, the solder joint strength of the epoxy resin composite Sn-Bi lead-free solder paste obtained in Example 2 is still higher than that of the Sn-Bi lead-free solder paste obtained in Comparative Example 2. Figure 4 It can be seen that the epoxy resin composite Sn-Bi lead-free solder paste obtained in Example 2 has a solder joint shear strength increased from 33.77N to 50.31N relative to the Sn-Bi lead-free solder paste obtained in Comparative Example 2, with an increase of more than 48.9%. After 1000 cycles of thermal shock test, the solder joint strength of the epoxy resin composite Sn-Bi lead-free solder paste obtained in Example 2 is still higher than that of the Sn-Bi lead-free solder paste obtained in Comparative Example 2. It can be seen that the epoxy resin composite Sn-Bi solder paste obtained in Example 2 not only has good wetting and spreading performance, but also can significantly improve the shear strength and reliability of the solder joint, especially the high temperature and high humidity reliability and thermal shock reliability, and can be used for reflow soldering of components in the electronics industry.
[0089] Example 3
[0090] The difference from Example 1 is that:
[0091] The commercially available Sn-Bi lead-free solder paste EcoLM-C10X used contains 90wt% Sn-Bi alloy powder and the remaining flux ECO Flux 823. In the Sn-Bi alloy powder, Bi element accounts for 58wt% of the alloy powder, P accounts for 0.05wt%, and the remaining is Sn. In addition, the alloy powder particle diameter is 15μm to 65μm.
[0092] In the epoxy resin composition, the epoxy resin is a combination of NPEL-127H type bisphenol A and E44 type bisphenol A in a mass ratio of 1:0.5; the curing agent is a combination of aromatic polyamine, alicyclic polyamine and dicyandiamide in a mass ratio of 1:1:1; the accelerator is a combination of SH-A80, SH-A85, SH-A90 and SH-A95 in a mass ratio of 1:1:0.5:1. The mass ratio of the epoxy resin, the curing agent and the accelerator is: epoxy resin: curing agent: accelerator = 100:15:1.5.
[0093] The obtained epoxy resin composite Sn-Bi lead-free solder paste contains 0.1wt% Ag, 0.1wt% Ga, 5wt% epoxy resin composition, and the remainder is commercially available Sn-Bi lead-free solder paste EcoLM-C10X.
[0094] Comparative Example 3
[0095] The difference from Example 3 is that no Ag powder, Ga metal and epoxy resin composition are added to the commercially available Sn-Bi lead-free solder paste EcoLM-C10X.
[0096] The reflow evaluation results of Example 3 and Comparative Example 3 are shown in Figure 5 and Figure 6 .Depend on Figure 5 It can be seen that the epoxy resin composite Sn-Bi lead-free solder paste obtained in Example 3 has a solder joint shear strength increased from 33.77N to 50.73N compared with the Sn-Bi lead-free solder paste obtained in Comparative Example 3, with an increase of more than 50%. After high temperature and high humidity aging for 1000h, the solder joint strength of the epoxy resin composite Sn-Bi lead-free solder paste obtained in Example 3 is still higher than that of the Sn-Bi lead-free solder paste obtained in Comparative Example 3. Figure 6 It can be seen that the epoxy resin composite Sn-Bi lead-free solder paste obtained in Example 3 has a solder joint shear strength increased from 33.77N to 50.73N relative to the Sn-Bi lead-free solder paste obtained in Comparative Example 3, with an increase of more than 50%. After 1000 cycles of thermal shock test, the solder joint strength of the epoxy resin composite Sn-Bi lead-free solder paste obtained in Example 3 is still higher than that of the Sn-Bi lead-free solder paste obtained in Comparative Example 3. It can be seen that the epoxy resin composite Sn-Bi solder paste obtained in Example 3 not only has good wetting and spreading performance, but also can significantly improve the shear strength and reliability of the solder joint, especially the high temperature and high humidity reliability and thermal shock reliability, and can be used for reflow soldering of components in the electronics industry.
[0097] Example 4
[0098] The difference from Example 1 is that:
[0099] The commercially available Sn-Bi lead-free solder paste EcoLM-C10X contains 88wt% Sn-Bi alloy powder and the remainder flux LFD, and in the Sn-Bi alloy powder, Bi element accounts for 56.5wt% of the alloy powder, P accounts for 0.01wt%, and the remainder is Sn. In addition, the alloy powder particle diameter is 15μm to 65μm.
[0100] The epoxy resin composition comprises NPEL-134 phenolic epoxy resin, NPEL-127H bisphenol A, E44 bisphenol A and E51 bisphenol A in a mass ratio of 1:1:1:1; the curing agent comprises alicyclic polyamine and dicyandiamide in a mass ratio of 1:1; and the accelerator comprises SH-A90 and SH-A95 in a mass ratio of 2:1. The mass ratio of the epoxy resin, the curing agent and the accelerator is: epoxy resin: curing agent: accelerator = 100:25:6.
[0101] The obtained epoxy resin composite Sn-Bi lead-free solder paste contains 0.5wt% Ag, 0.01wt% Ga, 7wt% epoxy resin composition, and the remainder is commercially available Sn-Bi lead-free solder paste EcoLM-C10X.
[0102] Comparative Example 4
[0103] The difference from Example 4 is that no Ag powder, Ga metal and epoxy resin composition are added to the commercially available Sn-Bi lead-free solder paste EcoLM-C10X.
[0104] The reflow evaluation results of Example 4 and Comparative Example 4 are shown in Figure 7 and Figure 8 .Depend on Figure 7 It can be seen that the epoxy resin composite Sn-Bi lead-free solder paste obtained in Example 4 has a solder joint shear strength increased from 33.77N to 52.68N compared with the Sn-Bi lead-free solder paste obtained in Comparative Example 4, with an increase of more than 56%. After high temperature and high humidity aging for 1000h, the solder joint strength of the epoxy resin composite Sn-Bi lead-free solder paste obtained in Example 4 is still higher than that of the Sn-Bi lead-free solder paste obtained in Comparative Example 4. Figure 8It can be seen that the epoxy resin composite Sn-Bi lead-free solder paste obtained in Example 4 has a solder joint shear strength increased from 33.77N to 52.68N relative to the Sn-Bi lead-free solder paste obtained in Comparative Example 4, with an increase of more than 56%. After 1000 cycles of thermal shock test, the solder joint strength of the epoxy resin composite Sn-Bi lead-free solder paste obtained in Example 4 is still higher than that of the Sn-Bi lead-free solder paste obtained in Comparative Example 4. It can be seen that the epoxy resin composite Sn-Bi solder paste obtained in Example 4 not only has good wetting and spreading performance, but also can significantly improve the shear strength and reliability of the solder joint, especially the high temperature and high humidity reliability and thermal shock reliability, and can be used for reflow soldering of components in the electronics industry.
[0105] It should be noted that the above preferred embodiments are only used to illustrate the present invention, but the present invention is not limited to the embodiments. Within the scope of the present invention, changes and modifications made by ordinary technicians in this field all belong to the protection scope of the present invention.
Claims
1. An epoxy resin composite Sn-Bi lead-free solder paste, characterized in that: Calculated by mass percentage, it contains the following components: Epoxy resin composition, 3%-10%; Ag powder, 0.001% to 1.5%; Metal Ga, 0.001% ~ 0.5%; Sn-Bi lead-free solder paste, balance; The epoxy resin composition is composed of epoxy resin, curing agent and accelerator in a mass ratio of 100:10-32:0.5-8.
2. The epoxy resin composite Sn-Bi lead-free solder paste according to claim 1, characterized in that: The mass percentage of the epoxy resin composition is 3%, the mass ratio of the epoxy resin, the curing agent and the accelerator is: epoxy resin: curing agent: accelerator = 100: 10: 0.5, the Ag powder is 0.001%, and the metal Ga is 0.5%.
3. The epoxy resin composite Sn-Bi lead-free solder paste according to claim 1, characterized in that: The mass percentage of the epoxy resin composition is 5%, the mass ratio of the epoxy resin, the curing agent and the accelerator is: epoxy resin: curing agent: accelerator = 100: 15: 1.5, the Ag powder is 0.1%, and the metal Ga is 0.1%.
4. The epoxy resin composite Sn-Bi lead-free solder paste according to claim 1, characterized in that: The mass percentage of the epoxy resin composition is 7%, the mass ratio of the epoxy resin, the curing agent and the accelerator is: epoxy resin: curing agent: accelerator = 100: 25: 6, the Ag powder is 0.5%, and the metal Ga is 0.01%.
5. The epoxy resin composite Sn-Bi lead-free solder paste according to claim 1, characterized in that: The mass percentage of the epoxy resin composition is 10%, the mass ratio of the epoxy resin, the curing agent and the accelerator is: epoxy resin: curing agent: accelerator = 100: 32: 8, the Ag powder is 1.5%, and the metal Ga is 0.001%.
6. The epoxy resin composite Sn-Bi lead-free solder paste according to claim 1, characterized in that: The epoxy resin includes at least one of NPEL-134 novolac epoxy resin, NPEL-127H bisphenol A, E44 bisphenol A and E51 bisphenol A.
7. The epoxy resin composite Sn-Bi lead-free solder paste according to claim 1, characterized in that: The curing agent includes at least one of aromatic polyamines, alicyclic polyamines and dicyandiamide.
8. The epoxy resin composite Sn-Bi lead-free solder paste according to claim 1, characterized in that: The accelerator includes at least one of SH-A80, SH-A85, SH-A90 and SH-A95.
9. The epoxy resin composite Sn-Bi lead-free solder paste according to claim 1, characterized in that: The Sn-Bi lead-free solder paste is a Sn-Bi lead-free solder paste containing P, and the Sn-Bi lead-free solder paste contains 85% to 95wt% of Sn-Bi alloy powder and the remainder of soldering flux.
10. The epoxy resin composite Sn-Bi lead-free solder paste according to claim 9, characterized in that: In the Sn-Bi alloy powder, by mass percentage, the Bi element content is 33% to 60%, the P content is 0.001% to 0.1%, and the balance is Sn.
11. The epoxy resin composite Sn-Bi lead-free solder paste according to claim 10, characterized in that: The particle diameter of the Sn-Bi alloy powder is 15 μm to 65 μm.
12. The epoxy resin composite Sn-Bi lead-free solder paste according to claim 9, characterized in that: The soldering flux is ECO Flux 823 or LFD.
13. The epoxy resin composite Sn-Bi lead-free solder paste according to claim 1, characterized in that: The particle diameter of the Ag powder is 15 μm to 65 μm.
14. The epoxy resin composite Sn-Bi lead-free solder paste according to claim 1, characterized in that: The adding temperature of the metal Ga is 80°C±5°C.
Citation Information
Patent Citations
Epoxy resin containing composite Sn-Bi unleaded soldering paste
CN108971794A
Tin-bismuth jet printing soldering paste modified by silver powder particles and preparation method thereof
CN107825001A
Epoxy resin composite Sn-Bi lead-free soldering paste
CN109175771A
Sn-BASED SOLDER ALLOY
JP2004188453A